IoT in Execution at John Deere - Innovation Leadership in What is Perceived to Be an Old Industry - Markus Beinert; Heiko Nies; Andreas Vermehren Schmiedel (Marketing Review St.Gallen, 2020)
Firms should not only focus on technological issues of the Internet of Things (IoT) for further enhancing the customer experience. They should also deal with implementation issues in their IoT ecosystems. For John Deere, one of the major players in the agricultural equipment industry, dealers have a critical role in the ecosystem. Besides offering advanced IoT technologies, John Deere also deploys innovative methods for advancing IoT services and experimenting together with its distribution channel partners. This article outlines challenges of implementing IoT-related services together with dealers, success factors and lessons to be learned from this case study.
Keywords: 650